Press Conference and Vigil re Protesting Jerry Falwell Speaking at Piccadilly Inn Airport - Watkins, Howard::::::::: (1984)
Protesters with handmade signs :God Doesn't Take Sides; Falwell Does" and "Falwell is the New Hitler …"